Assessment of slow rusting resistance components to stripe rust pathogen in some exotic wheat germplasm - P.K. SINGH, HARIKRISHNA, R.C. MATHURIA, R. GOGOI; R. AGGARWAL, VAIBHAV K. SINGH*, G.P. SINGH (Indian Phytopathology, 2017)
Stripe rust caused by Puccinia striiformis f. sp. tritici is one of the most destructive diseases of wheat. It is emerging as an important constraint to wheat production worldwide and northern India. Host resistance is the most economical way of controlling respective pathogen. However, race-specific resistance is overcome by the evolution of new races of the pathogens. Conversely, race non-specific or quantitative resistance, controlled by many genes and effective at the adult plat stage, is generally considered more durable and long lasting. Such type of resistance is of primary interest to wheat breeders around the world. With this background, experiments were conducted to assess the levels of slow rusting/adult plant resistance in exotic wheat germplasm (CIMMYT Mexico Core Germplasm Panel, CIMCOG). Sixty two exotic wheat germplasm including susceptible checks were evaluated against yellow rust for resistance both at seedling as well as adult plant stages. Slow rusting/partial resistance/adult plant resistance was assessed under field conditions through host response and epidemiological parameters estimates i.e., final rust severity (FRS), coefficient of infection (CI), relative area under disease progress curve (rAUDPC) and apparent infection rate (r). Promising slow rusting resistance was observed on the germplasm viz., CIMCOG 1, 2, 3, 5, 6, 7, 12, 14, 15, 17, 18, 20, 21, 22, 26, 27, 28, 29, 32, 33, 34, 35, 36, 38, 40, 43, 46, 47, 49, 52, 53, 58, 59 and 60 consistently during rabi seasons of 2013-16. All these promising stripe rust resistant germplasm at adult plant stage were susceptible at seedling stage to yellow rust, which indicated presence of slow rusting resistance among the germplasm. Significant diversity was observed for level of slow rusting resistance among the CIMMYT core wheat germplasm, which may be exploited in further breeding strategies to develop consistent and durable resistant varieties against stripe rust in India.